Static, Dynamic, and High Cycle Fatigue Analysis of Crossed Spherical Gearing for Robotic Arm Ball Joint: A Finite Element Analysis Approach - Serna-Landivar, José L.; Risco Sernaqué, Madelaine Violeta; Rivas Moreano, Ana Beatriz; Algoner, William C.; Anticona-Valderrama, Daniela M.; Zúñiga Porras, Walter Enrique; Oliva Guevara, Carlos (International Journal of Online and Biomedical Engineering (iJOE), 2024)
Crossed spherical gearing is used in the joints of robotic arm prostheses and allows mobility in 3 degrees of freedom. This paper aims to evaluate the design of a cross-spherical gear with three different materials, PEEK, AISI 304L, and Ti-6Al-4V, for a robotic arm prosthesis by finite element analysis. ANSYS mechanical software (version 2021 R1) was used to perform the static analysis and evaluate the deformations and stresses, modal analysis of natural frequencies and vibration modes, and high cycle fatigue analysis to determine fatigue resistance. The results obtained in the static analysis show that the maximum stresses are in the same zones for the three materials and have similar values. However, the Ti-6Al-4V and ASI 304L materials have a higher safety factor than PEEK, with a value of 5.17. In conclusion, the crossed spherical gearing is numerically validated using the finite element analysis so that the prototype can be later manufactured at an experimental level, and the values obtained for the crossed spherical gearing of the robotic arm prosthesis can be verified.